Classification of Slopes & Their Impacts for Movement of Materials In Hareer Flexure - SALMAN, NEERAN MAHMOOD (Al-Adab Journal, 2021)
The research aims to classify the slopes of Hareer Flexture and their effects on the movement of materials in their slopes. Al-Tayyah is located in the governorate of Erbil, Shaqlawa district, Hareer neighborhood in northeastern Iraq, between latitude (36 ° 25'10.0 ") and (36 ° 36'15.0") north, and two arcs of length (44 ° 19'34.0 ") and (44 29'16.0 '') to the east. It is a convex flexture extending northwest-southeast and submersible towards the axis of the flexture towards the northwest to one direction. The area of ​​the flexture is 94 square meters with length of 24 km. The height of its highest peak is 11.5 meters. It is called the summit of (Zentier). Geologic formations were exposed in the flexture. Which are Tanjiru - Shiransh formations and Palembo - Aqrah formations. The classification of the slopes and the movement of materials in the flexture was studied in a quantitative - descriptive manner. It was found that there are slow movements at the slopes, but continuous, as well as simple minor slips. That it was possible to be fast. Although its materials were not saturated with water. Which resulted in the shape of the convex slope in the flexture, thus the flexture was in the youth stage of its diatonic successive cycle. As the views of Alan Wood, Feynman and Lawson were analyzed in how the shapes of the flexture slopes were formed. As well as the steepness angles of the flexture were classified in comparative classification according to classifying both (Demek, 1979) and (Zink, 1989).